Comparative Theoretical Analysis Of Expectations In Different Psychological Concepts - Harutyunyan, Naira (Զանգակ հրատ.)
Our life is a chain of expectations according to which we live and act, and we create interpersonal relations, set goals and try to achieve them. Our expectations accompany us at all stages of life, in all aspects of interpersonal relationships, and all aspects of social perception. Different authors differ in terms of the phenomenon of expectation. However, at first glance, the problem of expectations in modern humanitarian sciences is not sufficiently studied, and there is no more or less conciliatory approach to determining expectations. This article aims to figure out how the expectations are defined, which phenomenological field they belong to, their content, with what other phenomena they are connected to, and so on?
Keywords: Psychology